The epidemiology and control of leishmaniasis in Andean countries - Clive Richard Davies; Richard Reithinger; Diarmid Campbell-Lendrum; Dora Feliciangeli; Rafael Borges; Noris Rodriguez
This paper reviews the current knowledge of leishmaniasis epidemiology in Venezuela, Colombia, Ecuador, Peru, and Bolivia. In all 5 countries leishmaniasis is endemic in both the Andean highlands and the Amazon basin. The sandfly vectors belong to subgenera Helcocyrtomyia, Nyssomiya, Lutzomyia, and Psychodopygus, and the Verrucarum group. Most human infections are caused by Leishmania in the Viannia subgenus. Human Leishmania infections cause cutaneous lesions, with a minority of L. (Viannia) infections leading to mucocutaneous leishmaniasis. Visceral leishmaniasis and diffuse cutaneous leishmaniasis are both rare. In each country a significant proportion of Leishmania transmission is in or around houses, often close to coffee or cacao plantations. Reservoir hosts for domestic transmission cycles are uncertain. The paper first addresses the burden of disease caused by leishmaniasis, focusing on both incidence rates and on the variability in symptoms. Such information should provide a rational basis for prioritizing control resources, and for selecting therapy regimes. Secondly, we describe the variation in transmission ecology, outlining those variables which might affect the prevention strategies. Finally, we look at the current control strategies and review the recent studies on control.